OIL-SARDINE IN THE ESTUARIES OF NORTH KANARA - Raja, B T Antony (Indian Journal of Fisheries, 2011)
Juveniles of Sardinella longkeps with modal sizes of 90 and 110 mm appeared in Kalinadi estuary during October, 1972. This may represent a passive incursion with the high-tide into the proximate river mouth. Similar instances were also reported at Aghanasfaini and Sharavati estuaries of North Kanara